Chemical and molecular analysis of the pheromone phenylacetonitrile in desert locust, Schistocerca gregaria Forskål (Orthoptera: Acrididae) - Scholtz, Clarke H. (University of Pretoria, 2021)
Thesis (PhD)--University of Pretoria, 2013.